A People's Green New Deal - Ajl, Max (Pluto Press, 2021)
The idea of a Green New Deal was launched into popular consciousness by US Congressperson Alexandria Ocasio-Cortez in 2018. Evocative of the far-reaching ambitions of its namesake, it has become a watchword in the current era of global climate crisis. But what - and for whom - is the Green New Deal? In this concise and urgent book, Max Ajl provides an overview of the various mainstream Green New Deals. Critically engaging with their proponents, ideological underpinnings and limitations, he goes on to sketch out a radical alternative: a 'People's Green New Deal' committed to degrowth, anti-imperialism and agro-ecology. Ajl diagnoses the roots of the current socio-ecological crisis as emerging from a world-system dominated by the logics of capitalism and imperialism. Resolving this crisis, he argues, requires nothing less than an infrastructural and agricultural transformation in the Global North, and the industrial convergence between North and South. As the climate crisis deepens and the literature on the subject grows, A People's Green New Deal contributes a distinctive perspective to the debate.